2018
DOI: 10.1039/c8ta05911j
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking sodium-ion anodes as nucleation layers for anode-free batteries

Abstract: The anode-free sodium battery with a nucleation layer is presented as a low-cost, high-performance option for stationary electric storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 45 publications
2
59
0
Order By: Relevance
“…For planar Cu, it reaches 46.3, 193.7 mV at 0.5, 2.0 mA cm −2 , respectively (Figure S5a, Supporting Information). When the current density is increased to 4.0 mA cm −2 , dramatic voltage fluctuation originating from the amplified heterogeneity in ionic distribution can be observed . In contrast, the pure CNF and D‐HCF electrode exhibits low nucleation overpotentials of 17.2, 21.3, 34.3 mV (Figure S5b, Supporting Information) and 7.1, 9.7, 16.4 mV at 0.5, 2.0, and 4.0 mA cm −2 (Figure b), respectively, which indicates the effective ion regulation enabled by D‐HCF even under high rates.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For planar Cu, it reaches 46.3, 193.7 mV at 0.5, 2.0 mA cm −2 , respectively (Figure S5a, Supporting Information). When the current density is increased to 4.0 mA cm −2 , dramatic voltage fluctuation originating from the amplified heterogeneity in ionic distribution can be observed . In contrast, the pure CNF and D‐HCF electrode exhibits low nucleation overpotentials of 17.2, 21.3, 34.3 mV (Figure S5b, Supporting Information) and 7.1, 9.7, 16.4 mV at 0.5, 2.0, and 4.0 mA cm −2 (Figure b), respectively, which indicates the effective ion regulation enabled by D‐HCF even under high rates.…”
Section: Resultsmentioning
confidence: 93%
“…When the current density is increased to 4.0 mA cm −2 , dramatic voltage fluctuation originating from the amplified heterogeneity in ionic Small 2019, 15,1902688 distribution can be observed. [54,55] In contrast, the pure CNF and D-HCF electrode exhibits low nucleation overpotentials of 17. (Figure 4b), respectively, which indicates the effective ion regulation enabled by D-HCF even under high rates.…”
Section: Resultsmentioning
confidence: 99%
“…Cohn et al have also demonstrated anode‐free sodium batteries pairing a sodiated Na 3 V 2 (PO 4 ) 3 cathode with an aluminum current collector coated with various thin nucleation layers. [ 104 ] Among the different nongraphitic carbons and sodium‐alloying metals evaluated as nucleation layers, carbon black and bismuth showed the highest Coulombic efficiencies for sodium plating and stripping. With a 1 m NaPF 6 in diglyme electrolyte and carbon black as the nucleation layer, the authors demonstrated a remarkable capacity retention of 82.5% after 100 cycles (NIRR = 99.8%) at a reasonable 0.5 mA cm −2 current rate and a 1.26 mAh cm −2 sodium plating capacity.…”
Section: Anode‐free Sodium Batteriesmentioning
confidence: 99%
“…[4][5][6] To solve such problems of Na metal electrodes,e fforts have been proposed such as manipulating nanostructured scaffolds, [7][8][9][10][11][12] optimizing electrolyte, [13][14][15][16] and engineering artificial protection layers. [17][18][19] Unfortunately,t hese progresses are still difficult to meet the demands of practical applications of Na metal electrodes. [20] In general, inhomogeneous Na deposition is largely determined by uneven distribution of current density,N a + / electron transport kinetics,a nd sodiophilcity (nucleation barrier or local potential).…”
Section: Introductionmentioning
confidence: 99%